Solar Cells: Ionic Liquid Control Crystal Growth to Enhance Planar Perovskite Solar Cells Efficiency (Adv. Energy Mater. 20/2016). Issue 20 (October 2016) - Seo, Ji‐Youn; Matsui, Taisuke; Luo, Jingshan; Correa‐Baena, Juan‐Pablo; Giordano, Fabrizio; Saliba, Michael; Schenk, Kurt; Ummadisingu, Amita; Domanski, Konrad; Hadadian, Mahboubeh; Hagfeldt, Anders; Zakeeruddin, Shaik M.; et al.
Abstract : In article number 1600767, Antonio Abate and co‐workers report a method to obtain a compact perovskite layer with larger grains, aiming for high performance perovskite solar cells with 19.5% power conversion efficiency. The image shows the mechanism of controlling perovskite crystal growth with ionic liquid, methylammonium formate (MAF). MAF can selectively interact with Pb, which can retard PbI2 ‐methylammonium iodide (MAI) interaction to form perovskite.